In Case of Fire in a Foreign Land : New and Collected Poems from Two Languages - Dorfman, Ariel (Book collections on Project MUSE., 2002)
A collection of poetry bearing witness to atrocities committed by the Chilean dictatorship, describing the realities and aftermath of terror.